2004
DOI: 10.1038/sj.ijo.0802598
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of food intake patterns and obesity in adult Danish men and women

Abstract: OBJECTIVE:The aim of this study was to test the hypothesis that specific food intake patterns or changes in food intake patterns were related to future changes in body mass index (BMI). DESIGN: Longitudinal observational study, with clinical and questionnaire examinations at baseline and two follow-up surveys, after 5 and 11 years. SUBJECTS: In all, 3785 men and women attended at baseline, of which 2436 aged 30-60 y attended all three examinations. MEASUREMENTS: A 26-item food frequency questionnaire, standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 31 publications
6
74
2
3
Order By: Relevance
“…12,13,19,[29][30][31][32] The percentage of variance of dietary intake (B16%) explained by these dietary patterns was similar in magnitude to what has been reported in other studies. 22,31,[33][34][35][36] Our results suggested that both patterns are associated with obesity phenotypes and odds of obesity. First, in this study, comparisons made across tertiles of factor scores showed positive associations between Western pattern scores and anthropometric indices whereas inverse associations were observed with the Prudent pattern scores.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…12,13,19,[29][30][31][32] The percentage of variance of dietary intake (B16%) explained by these dietary patterns was similar in magnitude to what has been reported in other studies. 22,31,[33][34][35][36] Our results suggested that both patterns are associated with obesity phenotypes and odds of obesity. First, in this study, comparisons made across tertiles of factor scores showed positive associations between Western pattern scores and anthropometric indices whereas inverse associations were observed with the Prudent pattern scores.…”
Section: Discussionmentioning
confidence: 50%
“…16 As, only few longitudinal studies have been performed to examine the link between dietary patterns and BMI or obesity. [17][18][19][20][21][22] Among them, one study found that food factors could not consistently predict changes in BMI or obesity development, 22 whereas the others showed that dietary patterns were significantly related to changes in BMI over time. [17][18][19]21 According to these studies, it seems that the adoption of a dietary pattern characterized by high intakes of red and processed meats, refined grains, sweets and desserts is associated with larger weight gain, whereas a dietary pattern usually characterized by high intakes of fruits, vegetables, whole grains, fish and poultry may facilitate weight maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The sweets and fats pattern we observed was somewhat close to the sweets pattern derived in the study by Tucker et al (22) , wherein a sweets pattern, which had high loadings from candy, sugar and chocolate candy, sweet baked goods and dairy desserts, was positively associated with waist circumference after adjustment for potential confounding. It also shares common elements with the sweets pattern in several other studies (11,12,23) , but no significant results were obtained. In the European Prospective Investigation into Cancer and Nutrition-Potsdam study (24) , higher intakes of sweets were predictive of weight gain over a 2-year follow-up period among men and women.…”
Section: Discussionmentioning
confidence: 74%
“…An approach which is becoming more and more widespread in nutritional research is the use of factor analysis, which has previously been used to investigate the influence of diet in adult life on risk of adverse outcomes (Gittelsohn et al, 1998;Slattery et al, 1998;Hu et al, 1999;Terry et al, 2001;Fung et al, 2003;Newby et al, 2004;Togo et al, 2004). Factor analysis has been employed in analysis of diet during pregnancy in a Spanish study (Cuco et al, 2006), where diet at different time points in pregnancy in relation to lifestyle factors was examined, and in a Mexican-American survey (Wolff and Wolff, 1995), where association between dietary patterns in pregnancy and birth weight was investigated.…”
Section: Introductionmentioning
confidence: 99%